The Effect of Cryopreservation on Human Sperm Growth Factors Expression: An Experimental Study - Saeednia, Sara; Ahmadiankia, Naghmeh; Fazli, Mozhgan; Shabani Nashtaei, Maryam; Babakhani, Abolfazl (Shahroud Journal of Medical Sciences, 2025)
Background: Cryopreservation is a widely employed assisted reproductive technology (ART) for the treatment of infertility. However, numerous sperm functions are compromised during the cryopreservation process. Considering the pivotal roles of nerve growth factor (NGF) and fibroblast growth factor (FGF) in sperm physiology and function, this study aimed to investigate the impact of cryopreservation on the expression and quality of these growth factors and their respective receptors.Methods: Semen samples were collected from 30 normozoospermic donors, with each sample divided into fresh and frozen-thawed groups. Sperm parameters were evaluated using computer-assisted sperm analysis (CASA). Real-time polymerase chain reaction (PCR) and Western blotting techniques were employed to quantify the gene and protein expression levels of growth factor receptors. Apoptosis was assessed using Annexin V staining, and enzyme-linked immunosorbent assay (ELISA) was conducted to measure levels of NGF and FGF2 in seminal plasma.Results: The findings demonstrated that the frozen-thawed group exhibited significantly reduced levels of fibroblast growth factor receptor 2 (FGFR2) and a trend towards decreased expression of tropomyosin receptor kinase A (TrkA) compared to the fresh group, although the latter was not statistically significant. Notably, the percentage of cells undergoing late apoptosis was markedly higher in the cryopreservation group relative to the fresh group. Furthermore, cryopreservation resulted in substantial reductions in NGF and FGF2 concentrations within the seminal plasma.Conclusions: The detrimental effects of freezing and thawing on the expression of growth factors and their receptors in sperm cells suggest that the integration of these factors during the cryopreservation process may enhance sperm quality post-thaw. Further research is warranted to explore the potential clinical applications of these findings.